Atomistic simulation of the trapping capability of He-vacancy defects at Ni ∑3(1 1¯ 2)[1 1 0] grain boundary. (13th October 2016) - Gong, Hengfeng; Wang, Chengbin; Zhang, Wei; Huai, Ping; Lu, Wei; Zhu, Zhiyuan
Abstract: He atoms tend to cluster and precipitate into bubbles that prefer to grow in the grain boundaries, resulting in high temperature He embrittlement with significantly degraded material properties. This is a major bottleneck in employing Ni-based alloys for applications such as molten salt reactors (MSRs). This paper focuses on understanding how the local grain boundary structure interacts with He atoms and how the local atomistic environment in the grain boundary influences the binding energy of He defects. Using molecular dynamics simulations, we have investigated the trapping capability of the Ni ∑ 3 ( 1   1 ¯   2 ) [ 1   1   0 ] grain boundary to He defects (He N ) and to He-vacancy defects (He N V M ). The two defects in the Ni grain boundary exhibit geometries with high symmetry. The binding energy of an interstitial He atom to He N V M defects is found to be generally larger in pure Ni than that in the grain boundary. We compared the binding energy of He N defects to the Ni vacancy and to the Ni grain boundary, finding that the Ni vacancy possesses a higher trapping strength to He N . We also found that the binding strength of He N to the grain boundary is stronger than that of He N V M to the grain boundary. The He-vacancy ratio in He N V M defects does not significantly affect the binding energy in the grain boundary plane. The current work will provide insight in understanding the experimentally observed He bubble formation in Ni-based alloys and bridge atomic scale events and damage with macroscopic failure.